TOWARDS A FLORA OF NEW GUINEA: OLEACEAE. PART 1. JASMINUM, LIGUSTRUM, MYXOPYRUM AND OLEA. - Ruth Kiew (Reinwardtia, 2020)
KIEW, R. 2020. Towards a Flora of New Guinea: Oleaceae. Part 1. Jasminum, Ligustrum, Myxopyrum and Olea. Reinwardtia 19(1): 1‒25. ‒‒ Oleaceae in New Guinea is represented by five genera and about 32 species, namely Chionanthus (about 16 species), Jasminum (10 species), Ligustrum (3 species), Myxopyrum (2 species) and Olea (1 species). A key to genera as well as descriptions of and keys to species of Jasminum, Ligustrum, Myxopyrum and Olea are provided. Of the three Ligustrum species, L. glomeratum is widespread throughout Malesia, L. novoguineense is endemic and L. parvifolium Kiew is a new endemic species. Six species of Jasminum are endemic (J. domatiigerum, J. gilgianum, J. magnificum, J. papuasicum, J. pipolyi and J. rupestre). Jasminum turneri just reaches the northern tip of Australia; of the two species from the Pacific Islands J. simplicifolium subsp. australiense just reaches SE Papua New Guinea and J. didymum, a coastal species, reaches into Malesia as far north as E Java; J. elongatum is widespread from Asia to Australia. Neither Myxopyrum species is endemic: M. nervosum subsp. nervosum extends from Peninsular Malaysia to Indonesian New Guinea, and M. ovatum from the Philippines to the Admiralty Islands. The sole species of Olea, O. paniculata, stretches from Java to Australia and New Caledonia.